2019
DOI: 10.3390/sym11030307
|View full text |Cite
|
Sign up to set email alerts
|

Finding College Student Social Networks by Mining the Records of Student ID Transactions

Abstract: Information about college students’ social networks plays a pivotal role in college students’ mental health monitoring and student management. While there have been many studies to infer social networks by data mining, the mining of college students’ social networks lacks consideration of homophily. College students’ social behaviors show significant homophily in the aspect of major and grade. Consequently, the inferred inter-major and inter-grade social ties will be erroneously omitted without considering suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Xu et al [30] calculate the counts of spatio-temporal cooccurrences of each student pair based on the transactions of students' campus cards. Instead of a fixed time-slicing method, the researchers acquire the co-occurrences events by using a sliding time-window method.…”
Section: B Inferring Social Connection On Spatio-temporal Co-occurrementioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [30] calculate the counts of spatio-temporal cooccurrences of each student pair based on the transactions of students' campus cards. Instead of a fixed time-slicing method, the researchers acquire the co-occurrences events by using a sliding time-window method.…”
Section: B Inferring Social Connection On Spatio-temporal Co-occurrementioning
confidence: 99%
“…Instead of using fixed time slices, inspired by the notion of the sliding window, we come up with a sliding prism approach to group trajectories into different resonance prisms for further analysis. The approach manages to avoid the event loss issues [30].…”
Section: B Sliding Prism For Co-occurrence Event Recordingmentioning
confidence: 99%
“…A day was divided into 144 10-min bins. Behavior time was therefore encoded as a number in the range [1,144], and we could not obtain the precise behavior time. Verification was performed by the student services department; they invited some students as volunteers to verify the experimental results.…”
Section: Privacy Protectionmentioning
confidence: 99%
“…These data describe students' daily behavior on campus from many aspects, which makes the multi-source behavior data available for in-depth analysis of their associations. Previous works based on behavior data has addressed topics such as constructing student social networks [1,2], predicting academic performance [3][4][5][6][7], and forecasting career choices [8]. These works showed that it is possible to analyze students' lives through their behavior data.…”
Section: Introductionmentioning
confidence: 99%
“…There is no unified measurement to evaluate the usefulness of rules. The traditional support-confidence framework is not applicable to mine HUNSR because it does not involve the utility measure [16][17][18].Furthermore, the utility-confidence framework in high utility association rule (HUAR) mining is not applicable either because it does not involve the ordinal nature of sequential patterns [19]. So, it is very important to formalize the problem properly and comprehensively.…”
Section: Introductionmentioning
confidence: 99%